Hayden White: Meaning and Truth in History - Hammond, David M. (Philosophy & theology, 1994)
Hayden White’s proposal that the meaning of historical writing is determined by the figure of speech (“trope”) which the historian applies to the data of research challenges a naive understanding of historical writing concerned merely with the presentation of past facts . To answer the charge that the poetic imposition of meaning does not allow for truthful representation of the Holocaust, White appeals to the knowable facts of the past which are then structured according to a figure of speech. He thus hopes to secure the element of ideology critique while maintaining that facts are arranged according ta the historian’s decision and not according to the historian’s understanding of what was, in Lonergan’s language, “going forward” in the past. This essay argues that, although meaning is not already present in the events of the past, neither is it simply imposed on these events by the historian’s trope. Lonergan’s more adequate construal of historical writing recognizes the dynamism of inquiry which rejects a naive view of facts, yet also argues for the possibility of truthful, albeit always partial, representations of events.